2017
DOI: 10.1002/art.39867
|View full text |Cite
|
Sign up to set email alerts
|

Human Endogenous Retroviral Genetic Element With Immunosuppressive Activity in Both Human Autoimmune Diseases and Experimental Arthritis

Abstract: The env59 gene has been adapted by the immune system as a control mechanism in autoimmunity. The peptides derived from the ISU domain contained in the Env59 protein may be useful as potentially new biologic treatments in rheumatic diseases such as SLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 44 publications
2
28
0
Order By: Relevance
“…It is, however, increasingly appreciated that immune reactivity to endogenous retroviruses may be part of an evolving co-adaptation process, which contributes to optimal function of host immunity [17]. As such, our previous data implies that the specific HERV-H envelope protein might have been adapted by the immune system to play a regulatory role in inflammation and that corresponding ISU peptide, here Env59-GP3, might present a template for drug development [19].…”
Section: Accepted Manuscriptmentioning
confidence: 87%
See 1 more Smart Citation
“…It is, however, increasingly appreciated that immune reactivity to endogenous retroviruses may be part of an evolving co-adaptation process, which contributes to optimal function of host immunity [17]. As such, our previous data implies that the specific HERV-H envelope protein might have been adapted by the immune system to play a regulatory role in inflammation and that corresponding ISU peptide, here Env59-GP3, might present a template for drug development [19].…”
Section: Accepted Manuscriptmentioning
confidence: 87%
“…The overall aim of this work was to examine the ability of the Env59-GPS ISU peptide to modify MS. Previous studies suggest that Env59-GP3 ISU peptide has significant immune regulatory and anti-inflammatory activity in vitro, ex vivo and in vivo in development of T-cell-mediated chronic autoimmune arthritis [19]. Furthermore, we have shown that the peptide is capable of inhibiting secretion of inflammatory cytokines, including IL-6, from stimulated Peripheral Blood Mononuclear Cells (PBMC) from either patients with SLE/RA or from healthy controls in vitro [19].…”
Section: Accepted Manuscriptmentioning
confidence: 91%
“…Besides HERV‐W, single‐nucleotide polymorphisms (SNPs) around HERV‐Fc1 showed a highly significant association with multiple sclerosis . HERV‐H/env59 protein was found to be upregulated in patients with systemic lupus erythematosus and negatively correlated with pathogenetic factors of human autoimmune rheumatic diseases …”
Section: Introductionmentioning
confidence: 99%
“…21 HERV-H/env59 protein was found to be upregulated in patients with systemic lupus erythematosus and negatively correlated with pathogenetic factors of human autoimmune rheumatic diseases. 22 Aberrant expression of various HERVs has been demonstrated in human cancer cell lines and primary tumor tissues, such as HERV-H, 23 HERV-K, 24 HERV-F, 25 HERV-R, 26 and HERV-S. 27 Rooney et al systematically mapped the RNA sequencing data from 18 different types of solid tumors to 66 HERV family members and identified numerous HERVs to show enhanced transcription in tumor tissues as compared with normal tissues. 28,29 Among them, a conservative set of three tumor-specific endogenous retroviruses (HERVH-5, HERVH48-1, and HERVE-4) all showed minimal to undetectable expression in normal tissues and elevated expression in tumor tissues.…”
mentioning
confidence: 99%
“…However, it is also conceivable that HERVs can exert immunosuppressive functions, mainly by means of env proteins. In fact, env contains an immunosuppressive (ISU) domain, and a pivotal study on SLE and RA patients, THP‐1 leukemia cell line and RA mouse models showed that the Env59 ISU peptide, belonging to HERV‐H3 locus, can exert immune‐modulatory effects on the expression of interleukin (IL)‐6 gene, IFN‐gamma and TLR7 (21). It seems that the tolerogenic properties of the Env59 ISU peptide derive from the polarization of resting macrophages (M0) toward a M2 phenotype, characterized by a strong production of IL‐10 and of other anti‐inflammatory mediators (22).…”
Section: Figmentioning
confidence: 99%